Characterising the association between positive hepatitis C virus antibody and pain among people who inject drugs. (16th August 2019) - Ng, Michelle; Hayashi, Kanna; Voon, Pauline; Shulha, Hennady P.; DeBeck, Kora; Milloy, M.‐J.; Ti, Lianping
Abstract: Introduction and Aims: People who inject drugs (PWID) are a key group within the hepatitis C virus (HCV) pandemic. Chronic pain is a common condition among PWID as these individuals are often exposed to soft tissue infections due to injections and violence. This study aims to characterise the relationship between HCV exposure and pain among PWID. Design and Methods: Data were derived from three prospective cohorts of PWID in Vancouver, Canada, between December 2011 and November 2016. The primary outcome was pain severity, which was defined based on the Euroqol EQ‐5D‐3L pain subscale. A bivariable and multivariable ordinal generalised estimating equations model was used to quantify the association between HCV exposure and pain among participants. Results: One thousand and twelve of 2038 participants (50%) reported moderate/extreme pain at baseline. In total, 1473 (72%) participants were HCV‐antibody positive. In unadjusted analyses, HCV exposure was positively associated with increased pain [odds ratio (OR) = 1.47; 95% confidence interval (CI): 1.20–1.81]. However, once adjusted for known confounders in multivariable analyses, HCV exposure did not remain significantly associated with increased pain (adjusted OR = 1.00; 95%CI: 0.78–1.28). Discussion and Conclusions: In this sample of PWID, HCV exposure was not significantly associated with pain once other factors were considered. These various factors may explain the elevated risk of pain among PWID and should be addressed in future initiatives when managing pain among PWID with HCV exposure. Future studies should also examine whether pain changes with changes in HCV status (i.e. active vs. cleared infection).